Measuring disaster recovery: bouncing back or reaching the counterfactual state?. Issue 3 (9th January 2015) - Cheng, Shaoming; Ganapati, Emel; Ganapati, Sukumar
<x xml:space="preserve">Abstract</x> How should one measure the recovery of a locale from a disaster? The measurement is crucial from a public policy and administration standpoint to determine which places should receive disaster assistance, and it affects the performance evaluation of disaster recovery programmes. This paper compares two approaches to measuring recovery: (i) bouncing back to pre‐disaster conditions; and (ii) attaining the counterfactual state. The former centres on returning to normalcy following disaster‐induced losses, whereas the latter focuses on attaining the state, using quasi‐experimental design, which would have existed if the disaster had not occurred. Both are employed here to assess two housing recovery indicators (total new units and their valuations) in Hurricane Katrina‐affected counties (rural and urban). The examination reveals significantly different outcomes for the two approaches: counties have not returned to their pre‐disaster housing conditions, but they do exhibit counterfactual recovery. Moreover, rural counties may not be as vulnerable as assumed in the disaster recovery literature.